Maternal Complications and Perinatal Mortality. Issue 2 (June 2015) - Vogel, J.P.; Souza, J.P.; Mori, R.; Morisaki, N.; Lumbiganon, P.; Laopaiboon, M.; Ortiz-Panozo, E.; Hernandez, B.; Pérez-Cuevas, R.; Roy, M.; Mittal, S.; Cecatti, J.G.; et al.
<x xml:space="preserve">Abstract</x> (BJOG. 2014;121(suppl 1):76–88)